Features of Rhetorical Organization in L2 Argumentative Essays by Chinese EFL Students at the Tertiary Level - Qi Fang; Lu Yu; Jiang Cheng (International Journal of TESOL Studies, 2020)
The current study employed The KEYHOLE Model (Baker, 1984) to analyze features of rhetorical organizations of 88 English argumentative essays written by Chinese university EFL students. The results indicated that 92% of sampled students employed deductive rhetorical organizations to compose their arguments, over 50% essays did not exhibit rhetorical coherence between supporting details and the thesis statement, and 34.1% sampled essays showed a discursive relationship between claims in the thesis statement and supporting details in body paragraphs. The 30 essays which did present supporting details to respond to the claim in the thesis statement, but only 10 essays indicated a high degree of rhetorical coherence between the thesis statement and its body paragraphs. The remaining 20 essays displayed a low degree of rhetorical coherence between the thesis statement and its body paragraphs. The majority of sample essays tended to use deductive rhetorical organizations but failed to achieve effectiveness in arguments. The instruction should be further focused on writing the thesis statement in the aspect of well-written rhetorical coherence. The findings suggest that L2 writing syllabi should design graded tasks on raising the Chinese students’ rhetorical awareness and skills for better intercultural communication.